The effect of storage temperatures and storage duration on the keeping quality of apple fruits cv. Golden Delicious grown under the environmental condition of El-Gabal El-Akhder area - Gadalla, Suleiman O. (Al-Mukhtar Journal of Sciences, 2003)
This study was conducted during the seasons of 2001 and 2002 on apple fruits (Malus domestica) cv. Golden Delicious grown under the environmental condition of eastern part of Libya, at El-Gabal El-Akhder (the green mountain) area to investigate the effect of storage temperatures, 0 , 3 and 5°C at 88±3% RH, on the keeping quality of the fruits for three different storage periods, 4 , 5 and 6 months. By following up the changes in acidity % (Malic acid) total soluble solid % firmness kg2, weight loss % and wastage % (due to physiological disorders and pathogens infection). The results indicated that fruits stored at 0°C had better quality, (greater retention of acidity, firmness and lower percentage of weight loss and wastage) than those stored at 5°C at the end of each the three different storage periods. Also the fruits stored at 0°C showed lower weight loss % and wastage than those stored at 3°C for 4 months, but by extending storage period for 5 or 6 months fruits stored at 0°C had better quality, (greater retention of acidity and firmness and lower percentage of weight loss and wastage) than those stored at 3°C. furthermore results indicated that, fruits stored at 0°C had better quality at 4 and 5 months storage period comparing with the third storage period for 6 months. Also the results indicated that the fruits stored at 3°C had better quality (greater retention of firmness with lower weight loss % and wastage %) than those stored at 5°C, at the each end of each the three storage periods. This study had proved that 0°C is the best temperature among those studied temperatures regime for storing Golden Delicious apple fruits for period not exceeded than 5 months.The high fruit quality of this cultivar greatly depended on weight loss % in this study fruits with high quality showed less than 4% water loss during storage, regardless to storage temperature and duration.